DIGITAL WELLBEING OF RESEARCH SCHOLARS: A COMPARATIVE STUDY OF CENTRAL UNIVERSITY OF SOUTH BIHAR AND MAGADH UNIVERSITY - Pandey, Rupesh Kumar; Hassan, Md. Mozammil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Digital Wellbeing (DW) is about crafting and maintaining a healthy relationship with technology. The widespread integration of digital technologies in education has transformed the teaching-learning landscape, offering unprecedented opportunities for accessibility, collaboration, and innovation. In this digital age, the research scholars of universities heavily depend on digital technologies for their research related activities like, accessing journals, research reports, conducting survey, data analysis, plagiarism checking, and report preparation. However, this digital dependency introduces challenges to their overall wellbeing, including mental, physical, and social aspects. This study investigates comparative analysis of the digital wellbeing of research scholars enrolled at the Central University of South Bihar (CUSB) and Magadh University (a state university of Bihar), focusing on their digital satisfaction, Safe and Responsible behaviour, and Digital Wellness. The respondents were sampled in the study to estimate the digital wellbeing of the research scholars enrolled in the different disciplines of both the universities. This study was based on the quantitative research approach using a standardised Digital Wellbeing Scale as Google form. The digital wellbeing of the research scholars of Central University of South Bihar and Magadh University were also compared considering their background variables. The findings of the study provide an insight towards digital wellbeing of research scholars of both the universities.